An estimate of cross-section of photo-proton reactions on ⁴⁷⁻⁵⁰Ti isotopes - Dikiy, N.P.; Zakharchenko, A.A.; Lyashko, Yu.V.; Uvarov, V.L.; Shevchenko, V.A.; Tenishev, A.Eh. (Вопросы атомной науки и техники, 2022)
Development of technology of isotope production at an electron accelerator, in particular ⁴⁷Sc by the ⁴⁸Ti(γ,p)⁴⁷Sc reaction, requires accurate data on cross-sections of this and other photo-proton reactions on the titanium isotopes, as the available data are characterized by considerable scatter. A simple technique for estimating maximum and width of the excitation function of a reaction with dominating giant dipole resonance was proposed and validated earlier. The method is based on measurement of normalized reaction yield in a thin target, overlapping completely a flux of X-rays, and processing of data obtained with the use of a developed analytical model. The joint activation of foils from natural nickel, molybdenum and titanium by bremsstrahlung radiation with end-point photon energy in the range 40…95 MeV was carried out. The characteristics of the reactions ⁴⁸Тi(γ,p)⁴⁷Sc, ⁴⁹Ti(γ,p)⁴⁸Sc, ⁵⁰Ti(γ,np)⁴⁸Sc, ⁴⁷Ti(γ,p)⁴⁶Sc, and ⁴⁸Ti(γ,np)⁴⁶Sc are studied by new technique. For verifying results, the wellexamined ⁵⁸Ni(γ,n)⁵⁷Ni and ¹⁰⁰Mo(γ,n) ⁹⁹Mo reactions, taking place in the nickel and molybdenum foils, are used.